Implementation of Literacy Tree Media In Improving Elementary School Students' Indonesian Language Learning Outcomes - Kadek Ayu Lestari; Ardhy Supraba; Muhammad Zulham (CV. Edujavare Publishing, 2026)
This study aims to improve Indonesian language learning outcomes by implementing the Literacy Tree model for fourth-grade students at Ponjalae Elementary School 7, Palopo City. This study is a Classroom Action Research (CAR) conducted at Ponjalae Elementary School 7, Palopo City. This classroom action research was conducted in cycles, consisting of Cycle I and Cycle II. The subjects in this study were 22 fourth-grade students. Data collection techniques used included tests, learning implementation observation sheets, and student activity observation sheets. The results of this study indicate that after two cycles of intervention, the average score of the Indonesian language learning outcome test using the Literacy Tree media for fourth-grade students at Elementary School 7 Ponjalae, Palopo City, increased in cycle I, resulting in an average individual score of 70.18 with a classical completion percentage of 63.64%. In cycle II, the average individual score was 88.4 with a classical completion percentage of 86.4%, an increase from cycle I. Therefore, it can be concluded that implementing the Literacy Tree media can improve the Indonesian language learning outcomes of fourth-grade students at Elementary School 7 Ponjalae, Palopo City.